Implementasi Ciri Khas Pendidikan Pesantren di SMPS Islam Terpadu Al-Hijrah 2 Laut Dendang - Nainggolan, Muhammad Afrizal; Sumanti, Solihah Titin; A, As’ad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of the characteristics of Islamic boarding school education at SMP S Islam Terpadu Al-Hijrah 2 Laut Dendang, which combines a modern education system with the distinctive values of Islamic boarding schools. The main focus of this study is to explore the policies underlying the implementation of Islamic boarding school education, the strategies and methods used, the obstacles faced, and the impact of its implementation on student character. This study uses a qualitative approach with data collection methods through observation, interviews, and documentation. The results of the study show that SMP S Islam Terpadu Al-Hijrah 2 Laut Dendang implements an integrated curriculum that integrates formal education and Islamic boarding schools. Activities such as halaqah, tahfidz, yellow book studies, and congregational prayers are the main elements in this education system. Teachers play an active role as educators and spiritual guides, while students are trained to develop discipline, noble morals, and independence. However, several obstacles are faced in this implementation, including limited facilities, variations in student backgrounds in understanding religion, strict time management, and lack of optimal support from some parents. However, various efforts have been made to overcome these obstacles, such as strengthening the role of teachers, involving the school community, and improving supporting facilities.